Trends in the development of cross-border trade in the Russian-Finnish borderlands - Stepanova, S. V.; Shlapeko, E. A. (Baltic Region, 2019)
This article considers the development of cross-border trade and tourism in the Russian- Finnish borderlands in the 19th/21st centuries. We describe the evolution of cross-border trade in the Russian-Finnish borderlands at different stages of the territory’s development. The patterns of cross-border trade have always been depended on the national policies of the two countries. Since the 19th century, cross-border trade in the Russian-Finnish borderlands has been the product of two factors. The first one is the demand from local residents for certain imported goods that are either absent or much more expensive in their own country. The second factor is the possibility of receiving additional or even basic income. We distinguish several periods (peddlar trade, Soviet-Finnish tourism, shuttle trade, shopping tourism) in the evolution of Russian-Finnish cross-border trade and identify their major trends and characteristics. We describe the general patterns of cross-border trade in these historical periods and juxtapose the pertinent institutional, organisational and infrastructural settings. We explain why the direction of the flow of finance and goods changed. Until the early 20th century, goods were brought to and money collected from Finland’s borderlands. Since the 1920s, the opposite situation has been observed. The latter trend has been growing in recent years. In this article, we aim at providing a periodisation and detecting the trends in and features of the evolution of cross-border trade in the Russian-Finnish borderlands in the 19th/21st centuries. To this end, we carry out a statistics and data analysis. We describe the Russian and international approaches to studying cross-border shopping tourism. We address Finland’s experience in stimulating inbound shopping tourism from Russia and examine why the Russians are attracted to the neighbouring state.